Experiments on the causation of the threat postures of Canada Geese - Blurton Jones, N G (Wildfowl, 1960)
A pair of Canada Geese had-reared in 1953 were used between 1955 and 1958 to test experimentally the hypothesis that certain display postures of this species are caused by a conflict between tendencies to attack and to flee from an opponent. The geese would follow and stay peacefully with the author if he was wearing a red sweater, corduroy trousers and Wellington boots. If he carried a stick or brush they would flee. If he wore a jacket they would attack vigorously. Thus it was possible to administer attack-evoking and escape-evoking stimuli simultaneously. When this was done the postures previously interpreted as threatening were elicited. When the attack-evoking stimulus was presented behind a fence which the geese had learned they could not get through, some but not all of the postures observed in the attack-flee conflict were seen. The experiments support the original hypothesis, which was based on non-experimental field observations.